EU renewable electricity law and policy : from national targets to a common market - Maxian Rusche, Tim <<[VerfasserIn]>> (Cambridge studies in european law and policy, 2015)
Regulation of renewable electricity in the internal electricity market : (still) a preserve of member states -- The regulatory options from an economic point of view: superiority of prices over quantities under real-world conditions -- The times they are a-changin'? The evolution of support schemes in member states over time -- Union law on state aid : down for the count, but not knocked out by PreussenElektra -- Union law on free movement of goods : the protection of the environment justifies (nearly) everything, except for "buy European" clauses for equipment -- Prohibition of internal customs duties and discriminatory taxation : the sometimes forgotten straightjacket -- 2013 to 2015 - Years of upheaval? -- Regulatory options for the creation of a common market -- Regulatory cross-fertilization across the Atlantic